New results on passivity-based H∞ control for networked cascade control systems with application to power plant boiler–turbine system. (August 2015) - Mathiyalagan, K.; Park, Ju H.; Sakthivel, R.
Abstract: This paper is concerned with the problem of passivity-based H ∞ controller design for a class of networked cascade control systems (NCCSs) with random packet dropouts. The NCCS under consideration is modeled by using state feedback controllers and the network-induced imperfections like packet dropouts and time-varying delays. The model is defined with a stochastic packet-dropout case by using the Bernoulli distributed white sequence with time-varying probability measures. The probability-dependent conditions for stabilization of NCCSs are established to guarantee the resulting closed-loop system to be stochastically stable and achieve a prescribed mixed H ∞ and passivity performance. The Lyapunov stability theory and linear matrix inequality (LMI) approach are used to derive criteria for the existence of the state feedback controllers. The proposed probability-dependent gain scheduled controller can be designed by solving the convex optimization problem by means of a set of LMIs, which can be easily solved by using some standard numerical packages. Finally, a practical application is presented to illustrate the effectiveness and potential of the proposed results.